A new species of the Gondwanan centipede Anopsobius (Chilopoda: Lithobiomorpha) from New South Wales, Australia - Edgecombe, Gregory D. (Zootaxa, 2003)
Anopsobius wrighti n. sp., from the New England and Washpool-Gibraltar Range regions of northern New South Wales, is the first Australian species of the Gondwanan genus Anopsobius Silvestri, 1899 (Henicopidae: Anopsobiinae). Anopsobius is also known from Chile, Argentina, the Falkland Islands, South Africa, New Zealand, and the Chatham and Auckland Islands. The new species is closely related to the New Zealand species A. neozelanicus Silvestri, 1909.